Impact of Pyridoxine Supplement on Oxidative Stress in Type 2 Diabetic Patients - Moatamad Hanoon Dawood; Manal Khalid Abdulridha; Hayder Saadoon Qasim (College of Pharmacy / Mustansiriyah University, 2024)
Background: The physiologically active form of vitamin B6 is pyridoxal 5-phosphate (PLP), which functions as a coenzyme in 150 enzymatic processes such amino acid, carbohydrate, and lipid metabolism and is essential for the production and/or breakdown of neurotransmitters. . It also acts as an antioxidant by quenching Reactive Oxygen Species (ROS) and counteracting the formation of Advanced Glycation End-Product (AGEs). PLP is recycled by mammals from B6 vitamins found in diet and has been linked to a number of clinically significant disorders. This study aim was to evaluate the impact of pyridoxine supplementation on oxidative stress status in type 2 diabetic patients. Method: This prospective controlled randomized open-labeled study of newly diagnosed T2DM patients. The study was conducted from November 2022 to February 2023 at the Mesan Center for Diabetes and Endocrinology under the supervision of a specialist endocrinologist. The total number of participants whose data were collected in this study was one hundred and eight participants, eighty-eight patients newly diagnosed with type 2 diabetes were included in the study, and twenty of the participants were healthy subjects. The patients were allocated into three groups: Group 1: Control group, 20 T2DM patients were treated with non-pharmacological therapy (lifestyle modification) for one month, Group 2: 34 T2DM patients treated with metformin 500 mg/day in addition to non-pharmacological therapy (lifestyle modification) for one month, Group 3: 34 T2DM patients treated with metformin 500 mg/day plus vitamin B6 300 mg/day in addition to non-pharmacological therapy (lifestyle modification) for one month, in addition to Healthy subjects: 20 subjects were taken to compare the study parameters between type 2 diabetic patients and healthy persons at baseline. Measurement of Vitamin B6 (pyridoxine) blood level (PLP), body mass index (BMI) and Serum malondialdehyde level (MDA) was done in this study. Results: The results of the study showed that the use of pyridoxine supplementation plus metformin decreased the level of MDA. There was significant decrease in (MDA) level (P<0.01) pretreatment when compared to after treatment (3.85 μmole/L vs 1.66 μmole/L) respectively. Conclusion: Restoration of vitamin B6 level can leads to a decreased blood level of MDA in diabetic patients.